2018
DOI: 10.4028/www.scientific.net/kem.771.118
|View full text |Cite
|
Sign up to set email alerts
|

Contact Melting of Aluminum-Silicon Structures under Conditions of Thermal Shock

Abstract: The work is devoted to the study of contact melting in the Al-Si system, which is an aluminum film deposited on a silicon single-crystal substrate. The impulse action of high-density currents (j> 8.1010 A / m2) passing through an aluminum film is analyzed. It was found that under the considered electric heat loads in the system, the degradation processes associated with the appearance of a molten aluminum zone and subsequent contact melting in the metal-semiconductor system develop. From the analysis of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The area of the obtained single-layer polycrystalline graphene is more than 99% of the total surface area. It should be noted that the thermal conductivity coefficient [9] of polycrystalline graphene will be lower than the thermal conductivity coefficient of the single crystal graphene shown in Fig. 3.…”
Section: T °Cmentioning
confidence: 80%
“…The area of the obtained single-layer polycrystalline graphene is more than 99% of the total surface area. It should be noted that the thermal conductivity coefficient [9] of polycrystalline graphene will be lower than the thermal conductivity coefficient of the single crystal graphene shown in Fig. 3.…”
Section: T °Cmentioning
confidence: 80%
“…Earlier (Skvortsov et al, 2018;Skvortsov et al, 2016a) we revealed that, at high-power electric pulses (pulse duration τ ~ 500 s and pulse power P i = 5…17 W), the degradation processes in the binary metallization systems are related to formation of a melted zone (when the metal melting temperature is achieved) and contact melting processes that occur at the metal-semiconductor interface.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of test structures was performed with optical photolithography (Figure 3, a-d). The investigation of test structures was made using the voltmeter-ammeter method from the electrical response taken from different structure areas in the passage of single current pulses of different forms (Skvortsov et al, 2018;Skvortsov et al, 2016b). The experimental investigation of degradation processes was performed for the test structures (Figure 3, e) from the switching oscillograms U(t).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 12 bonding pads (1–12, Fig. 1 a) registered the U(t) signal from different parts of the test structure [ 15 , 16 ]. Degradation processes were experimentally studied on test structures with an increasing amplitude of a rectangular current pulse j > 6 × 10 10 A/m 2 and duration τ > 500 μs.…”
Section: Methodsmentioning
confidence: 99%